Satiety and in vitro digestibility of low saturated fat Bologna sausages added of chia mucilage powder and chia mucilage-based emulsion gel. (February 2020) - Câmara, Ana Karoline Ferreira Ignácio; Geraldi, Marina Vilar; Okuro, Paula Kiyomi; Maróstica, Mário Roberto; da Cunha, Rosiane Lopes; Pollonio, Marise Aparecida Rodrigues
Graphical abstract: Highlights: Bologna sausages with chia mucilage have the same satiating capacity than control. Structural changes in sausages with mucilage were elucidated during a digestive process. Chia mucilage interfered in the protein digestibility of the Bologna sausages. Chia mucilage is an effective fat replacer and contributes to a higher perception of satiety. Abstract: The objective of this study was to evaluate the effects of the replacement of pork back fat by chia mucilage (MC) and a chia mucilage-based emulsion gel in Bologna sausages on the appetite sensations of healthy volunteers, and to investigate the microstructural changes during simulated in vitro digestion. Three treatments were made: FMC (10% fat and 4% MC); MC-EG (20% chia-mucilage-based emulsion gel); FC (20% fat as a control). The meals were served as breakfast after an overnight fast for 23 people. Similar appetite sensations were perceived by volunteers (P > 0.05) for all treatments. The microscopy images revealed a pronounced aggregation of the samples containing MC in the gastric phase. In conclusion, MC was an effective fat replacer with the same satiating capacity than pork back fat. Besides, MC demonstrated that it might interfere in protein digestibility, consequently increased retention time in the stomach, which may result in early satiety.